Root Endophytic Fungi Regulate Changes in Sugar and Medicinal Compositions of Polygonum cuspidatum - Sun, Rui-Ting; Feng, Xiang-Cao; Zhang, Ze-Zhi; Zhou, Nong; Feng, Hai-Dong; Liu, Yi-Mei; Hashem, Abeer; Al-Arjani, Al-Bandari Fahad; Abd_Allah, Elsayed Fathi; Wu, Qiang-Sheng (Frontiers in Plant Science, 2022)
Polygonum cuspidatum Sieb. et Zucc is an important industrial crop because it contains a large amount of medicinal secondary metabolites (such as polydatin, resveratrol, chrysophanol, and emodin). However, it is unclear whether root endophytic fungi increase the content of secondary metabolites in the plant. This study aimed to analyze the effects of Funneliformis mosseae (Fm) and Piriformospora indica (Pi) alone or in combination on plant growth, root morphology, thirteen sugars concentrations, and six secondary metabolites (physcion, chrysophanol, emodin, aloe-emodin, polydatin, and resveratrol) concentrations of P. cuspidatum. After 11 weeks of the fungal inoculation, the roots could be colonized by Fm and Pi single or in combination, along with the higher root colonization frequence of Fm > Pi > Fm+Pi in the descending order. In addition, Fm and Pi improved plant growth performance (plant height, stem diameter, leaf number, and shoot and root biomass) and root morphology (average diameter, maximum diameter, total length, area, and volume) to varying degrees, depending on fungal inoculations, in which Pi displayed a relatively better effect on plant growth. Single Fm and Pi inoculation significantly increased three disaccharides (sucrose, maltose, and trehalose) accumulation, while dual inoculum (Fm + Pi) only elevated sucrose concentrations. Most monosaccharides concentrations, such as D-arabinose, D-galactose, D-sorbitol, D-fructose, glucose, and L-rhamnose were not altered or inhibited by the endophytic fungi, except the increase in L-fucose and inositol. All fungal treatments significantly increased root chrysophanol and resveratrol concentrations, while decreased aloe-emodin concentrations. In addition, single Pi and dual Fm+Pi increased emodin concentrations, and single Fm and dual Fm+Pi elevated physcion and polydatin concentrations. It was concluded that Fm and Pi promoted the growth of P. cuspidatum, and the combination of Fm and Pi was more conducive to the production of some secondary metabolites than single inoculation.